Corporate social responsibility: adoption of green marketing by hotel industry - Punitha, S.; Mohd Rasdi, Roziah (Canadian Center of Science and Education, 2013)
This study which is based on a widespread review of literature discusses about adoption of green marketing by hotels as a mechanism to perform corporate social responsibility (CSR). This paper examines in detail the literature and theories surrounding CSR, Malaysian government's role in protecting the environment, the challenges of green marketing and the state of CSR within the hotel industry. The discussion reveals that hotels are found to be under constant pressure to balance the diverse forms of corporate social responsibility. By knowing the significance of sustainability, the Malaysian government has been encouraging the hotels and other sectors to embrace green technology and practices by providing incentives and tax breaks. Whilst hoteliers are striving to achieve financial performance by practicing green marketing, gaining the trust and meeting the expectations of the public have become more challenging. Further review discloses that strategy such as greenwashing needs to be avoided by hoteliers to gain the confidence among green consumers towards the green claims. The paper further concludes that green marketing is being used as a tool by hotels to perform their CSR while it provides competitive advantage for hotels in ensuring a balance between development and environmental sustainability.